2016
DOI: 10.1016/j.vaccine.2015.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Development of a candidate reference material for adventitious virus detection in vaccine and biologicals manufacturing by deep sequencing

Abstract: HighlightsDeep sequencing has potential as an improved adventitious virus screening method.15 laboratories sequenced a common reagent containing 25 target viruses.6 viruses were detected by all lab, the remainder were detected by 4–14 labs.A wide range of sample preparation and bioinformatics methods is currently used.A common reference material is essential to enable results to be compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 35 publications
0
46
0
Order By: Relevance
“…At an influenza A virus concentration of over 10 5 copies/ml, this dropped to just 0.5%, and at a reovirus concentration of 10 3 -10 4 copies/ml, no viral reads were detected 24 . With our method, whole genomes were obtained for those with the highest viral loads, and for minority viral targets, there was a correlation between ostensible quantity and coverage, including for two viruses undetectable by the panel distributor 42 , a result superior to that recently obtained from influenza in clinical respiratory samples 65 . Again, the presence of high quantities of one or more target is likely to have inhibited the representation of the minority species such that if tested individually, superior depths and coverages would seem likely.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…At an influenza A virus concentration of over 10 5 copies/ml, this dropped to just 0.5%, and at a reovirus concentration of 10 3 -10 4 copies/ml, no viral reads were detected 24 . With our method, whole genomes were obtained for those with the highest viral loads, and for minority viral targets, there was a correlation between ostensible quantity and coverage, including for two viruses undetectable by the panel distributor 42 , a result superior to that recently obtained from influenza in clinical respiratory samples 65 . Again, the presence of high quantities of one or more target is likely to have inhibited the representation of the minority species such that if tested individually, superior depths and coverages would seem likely.…”
Section: Discussionmentioning
confidence: 83%
“…The members of the multi-FASTA reference file for the BBV Panel were obtained by submitting FASTQ sets from the rRNA-depleted sample with the highest virus concentrations to the SPAdes-HMMER-mapping approach described in the previous paragraph. VMR Panel references were derived from sequences obtained from GenBank using accession numbers from Mee et al 42 . Additionally, the complete genome sequence of a human pegivirus (HPgV) present in the plasma diluent was discovered in the SPAdes contigs file.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the reasonable high values that could be detected using qPCR, indicated that the initial extraction was successful. Noroviruses have previously been documented to be difficult to detect using metagenomics [51,52] possibly because of the small genome, robust nucleocapsid, or inhibitory RNA secondary structures [53]. Virus species specific extraction efficiency biases are well documented in viral metagenomics [54] and should always be considered when interpreting the results.…”
Section: Discussionmentioning
confidence: 99%